A narrative study of patients' illness experiences on antiretroviral treatment - Tsope, Lindiwe (Rhodes University, Faculty of Humanities, Department of Sociology, 2018)
Eight female respondents, who have publicly disclosed their HIV-positive status on social media, were involved in a semi-structured in-depth interview process. Using the theoretical frameworks of symbolic interactionism and social constructionism, the study explores the effects of antiretroviral treatment on patients' illness experiences, looking at the personal and social symbolisms and meanings attached to taking antiretrovirals. The study revealed a positive and inspirational aspect of living with HIV/AIDS and especially consuming antiretroviral therapy. It became evident that the knowledge participants had of antiretrovirals before consuming them was misguided and based more on false 'general knowledge' among laypersons than actual medical fact. Moreover, the study revealed that there is a social reconstruction of narratives that has taken place in each participant's life due to consuming antiretrovirals. Publicly disclosing their statuses has also proved to have both negative and positive consequences for the individuals and for society at large. While there is a consensus that participants' illness experiences are directly affected by antiretroviral treatment, each participant's narrative is different, yet positive.
Keywords: AIDS (Disease) Social aspects -- South Africa; HIV infections Social aspects -- South Africa; Stigma (Social psychology); Antiretroviral agents; Disclosure of information; Social media in medicine -- South Africa; Discourse analysis, Narrative